Reclaiming Female Subjectivity: Intertextual Transformation from Balinese Kidung Jerum Kundangdia to Novel Jerum - Juliana, I Wayan; Suarka, I Nyoman; Darma Putra, I Nyoman; Suardiana, I Wayan (International Journal of Multidisciplinary Sciences, 2025)
This study critically examines the intertextual transformation from the Balinese Kidung Jerum Kundangdia to Oka Rusmini's Novel Jerum (2019), focusing on how this dialogue articulates women's emotional resistance against patriarchal constraints. It addresses a gap in understanding how traditional Nusantara narratives can be dynamically reinterpreted to foreground female subjectivity and agency. Employing a qualitative approach grounded in Riffaterre's semiotics, the research identifies the kidung as the generative hypogram. It traces how Rusmini's novel utilizes the shared matrix of satya (loyalty) while foregrounding semara (passionate love) as a model for emotional expression and resistance. Data, derived from close textual analysis and archival documentation of both primary sources, were analyzed through thematic content analysis and feminist discourse analysis. The findings demonstrate that Jerum critically reorients reader empathy towards the protagonist Ni Jerum's suppressed inner life, repositioning her as an active agent challenging societal norms. Simultaneously, the novel revitalizes core motifs from the kidung tradition for contemporary gender discourse. This research significantly contributes to Nusantara literary and gender studies by illustrating the dynamic reciprocity between source text and adaptation. It affirms the power of intertextual strategies within local traditions to advocate for women's emotional legitimacy and resistance, enriching the treasury of text-based gender analysis in the region.